2011
DOI: 10.1017/s1368980011001261
|View full text |Cite
|
Sign up to set email alerts
|

Universal iron supplementation: a simple and effective strategy to reduce anaemia among low-income, postpartum women

Abstract: Objective: To reduce prevalence of anaemia in low-income postpartum women. Design: A randomised, non-blind clinical trial was conducted among 959 lowincome, postpartum women in eleven clinics in Mississippi. The clinics were randomised to one of three treatment groups: (i) selective anaemia screening of high-risk women as recommended currently (control); (ii) universal anaemia screening and treatment of anaemic women (group I); and (iii) universal Fe supplementation of 65 mg/d for two months to all low-income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…There was also weak evidence that lower oral doses produced low rates of side-effects such as gastrointestinal symptoms. A more recent trial conducted in Mississippi demonstrated that while a systematic test-and-treat approach was better than test-and treat-among only high risk women, universal supplementation produced better hematologic outcomes than either of the other 2 groups[ 85 ]. Women in the control group (high risk pregnancy test-and-treat) had a rate of anemia at 6 months post-partum of 34% versus 43% in the systematic test-and-treat group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also weak evidence that lower oral doses produced low rates of side-effects such as gastrointestinal symptoms. A more recent trial conducted in Mississippi demonstrated that while a systematic test-and-treat approach was better than test-and treat-among only high risk women, universal supplementation produced better hematologic outcomes than either of the other 2 groups[ 85 ]. Women in the control group (high risk pregnancy test-and-treat) had a rate of anemia at 6 months post-partum of 34% versus 43% in the systematic test-and-treat group.…”
Section: Resultsmentioning
confidence: 99%
“…Women in the control group (high risk pregnancy test-and-treat) had a rate of anemia at 6 months post-partum of 34% versus 43% in the systematic test-and-treat group. The universal supplementation group had a rate of only 22.5% (p<0.001)[ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reticulocyte Hb is a clinically useful marker for determining iron deficiency and hematological responses during iron administration (47) and is an emerging biomarker as an alternative to biochemical iron studies in the diagnosis of IDA (48). There are newer regulators of iron homeostasis such as the hepatic peptide hormone hepcidin that are stimulated by inflammation (49). Serum hepcidin quantification assays are increasingly being used to both identify iron deficiency (50) and determine intestinal absorption response to iron administration (51).…”
Section: Differences Between Iron Deficiency and Idamentioning
confidence: 99%
“…(2012) tarafından Mississippi'de 11 sağlık ocağını kapsayan ve düşük gelirli popülasyon da anemiyi azaltmak için demir preparatlarının etkinliğini değerlendirmek amacıyla yapılan bir çalışmada, düşük gelirli tüm postpartum dönemdeki kadınlara iki ay boyunca 65 mg/gün demir preparatı verilmiş ve demir alan kadınlarda anemi insidansı anlamlı şekilde azalmış-tır. 41 Hodgins ve ark. (2016)'nın basit ve etkili müdahalelerin sonuçlarını incelemek amacıyla kanıta dayalı olarak derledikleri makalelerinde, demir preparatları için anemiyi tedavi ettiğine dair yeterli kanıt olmadığını belirtmişlerdir.…”
Section: Demi̇r Preparati Kullanimiunclassified